2009
DOI: 10.1093/geronb/gbp046
|View full text |Cite
|
Sign up to set email alerts
|

Age Identity, Gender, and Perceptions of Decline: Does Feeling Older Lead to Pessimistic Dispositions About Cognitive Aging?

Abstract: Age identity shapes cognitive aging dispositions, though the gendered nature of this relationship remains somewhat unclear. The findings give further evidence about the far-reaching implications of age identity for successful aging and suggest that future work can explicate how subjective aging processes may differ by gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 34 publications
11
87
0
2
Order By: Relevance
“…In other words, even though these women held high expectations and positive views of their own aging and positive stereotypes of old age, it did not mean they were more likely to engage in preventative health behaviors, such as physical activity, in later life. Recently, there has been a call for a more culturally relevant, domain-specific, gender-specific, multidirectional, and multidimensional perspective of aging experiences, feelings, and perceptions [5,24,[57][58][59][60]. With regard to gender differences, a quantitative study by Schafer and Shippee [58] found that feeling older led to more negative views about cognitive aging among women, but not men, aged 55 years and over.…”
Section: Emerging Qualitative Research Findingsmentioning
confidence: 99%
“…In other words, even though these women held high expectations and positive views of their own aging and positive stereotypes of old age, it did not mean they were more likely to engage in preventative health behaviors, such as physical activity, in later life. Recently, there has been a call for a more culturally relevant, domain-specific, gender-specific, multidirectional, and multidimensional perspective of aging experiences, feelings, and perceptions [5,24,[57][58][59][60]. With regard to gender differences, a quantitative study by Schafer and Shippee [58] found that feeling older led to more negative views about cognitive aging among women, but not men, aged 55 years and over.…”
Section: Emerging Qualitative Research Findingsmentioning
confidence: 99%
“…Society and culture are also a significant influence in the development of identity, meaning and expectations among individuals, but they also are a potential cause for gender disadvantages in health (Gorman & Read, 2006). In addition, the influence of culture is a significant factor in women's development of expectations, as it is partially responsible for the process in which women assign meaning to themselves as well as their ability to define their position within society (Schafer & Shippee, 2010).…”
Section: Age Identity and Attitudes Toward Agingmentioning
confidence: 99%
“…Although men are devalued as they age, women experience a harsher reality as their worth is defined by their attractiveness, beauty and being young; as a result, they may feel pressure to use products and get surgical procedures to hide the signs of aging. Furthermore, youthfulness is ideally viewed and prized among contemporary societies and contributes to the prevalence of ageism and negative stereotypes of aging, especially among older women as they are no longer positively evaluated on traits such as physical beauty and sexual attraction (Schafer & Shippee, 2010). As women get older, they are more vulnerable to being viewed as incapable, feeble, weak, and dependent as a result of age related changes, while men seem to retain their sense of vigor and strength that is associated with the male gender.…”
Section: Age Identity and Attitudes Toward Agingmentioning
confidence: 99%
See 2 more Smart Citations